Efficacy of a breastfeeding support education program for nurses and midwives: a randomized controlled trial - Izumi Sato; Masumi Imura; Yohei Kawasaki (BMC, 2022)
Abstract Background Nutritional support influences the growth and development of late preterm infants (LPIs) and their long-term health status. However, healthy LPIs have a shorter hospital stay and may not receive adequate care after discharge. In this study, we developed and evaluated the effectiveness of an educational program for nurses and midwives to enable them to support breastfeeding of healthy LPIs. Methods A randomized controlled trial was conducted in Japan from July 2018 to April 2019. The participant pool consisted of nurses and midwives working at midwiferies and obstetric centers in Tokyo, Japan. A total of 395 candidates were recruited for participation across 79 facilities. The final participants were assigned to two groups: the breastfeeding support for LPIs program (BSLPI group; n = 36) or the non-technical skills program (NTS group; n = 33). The measures included the Self-Efficacy of Breastfeeding Support scale (SBS), the Social Skills in Nursing Interactions with Mothers (SS) scale, and the Knowledge and Skills Necessary for Breastfeeding Support for LPIs test (K-S). Scores for each measure were collected before, after, and one-month after the intervention. Repeated-measures ANOVA was used to identify differences (main effects) according to program (BSLPI and NTS) and time (before, immediately after, and one month after intervention). Results All 69 participants attended the program. Main effects of the program were observed only for K-S scores (F[1,58] = 78.57, p = 0.01). No significant differences were found for SBS (F[1,58] = 0.63, p = 0.43) or SS scores (F[1,58] = 1.51, p = 0.23). Conclusions Participation in the BSLPI was related to improved breastfeeding support knowledge and skills but was not related to improvements in nurses' self-efficacy or social skills. Trial registration Registered 12 December 2018, https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000040145 (UMIN: UMIN000035227).